Production and perception of English consonants by Yemeni EFL learners of English - Hadjah, Najah Ahmed Khamis (2024)
Few previous studies on perception-production correlations employed acoustic measurements to assess production accuracy; most used transcriptions and native- English speaker evaluations. This study investigates Yemeni EFL learners’ production and perception of six English consonants using acoustic assessment. It aims to examine the extent to which (six) phonological processes occur in Yemeni EFL adult learners’ production of the target consonants, to investigate the extent to which word position and gender affect the production and perception of the examined consonants, and to assess the extent to which the production of each target consonant correlates with its perception. Data was collected quantitatively from Yemeni postgraduates at six Malaysian public universities. The speakers produced seventy-two words with the target consonants three times in isolation and three times in a carrier sentence. The researcher analysed the speakers’ productions via Praat after recording them with a smartphone. In the perception test, an AXB experiment was conducted. The results showed that the most frequent phonological process in the speakers’ production was devoicing, followed by stopping, voicing, deaffrication, velarisation, and then palatalisation. Moreover, word position significantly affected overall correct production/perception, the total correct production of /v/ and /dʒ/, and the total correct perception of /p/, /ð/, and /dʒ/. Furthermore, gender significantly affected the correct production/perception of all sounds, except /ʤ/, which reached significance. Lastly, the Pearson correlation test revealed that the correlation was moderate between overall production and perception, and between /p/ and /ð/ production and perception, strong between /v/ production and perception, and weak between /θ/, /ʧ/, and /ʤ/ production and perception. Briefly, many factors can affect the correlation between L2-sound production and perception, including word position and gender, besides the L1-L2 degree of similarity, which may cause several phonological processes that create miscommunication in L2 among speakers. The findings have implications for L2 speech and pronunciation instruction.